Kv1.5 Open Channel Block by the Antiarrhythmic Drug Disopyramide: Molecular Determinants of Block - Iván A. Aréchiga; Gabriel F. Barrio-Echavarria; Aldo A. Rodríguez-Menchaca; Eloy G. Moreno-Galindo; Niels Decher; Martin Tristani-Firouzi; José A. Sánchez-Chapula; Ricardo A. Navarro-Polanco (Elsevier, 2008)
Kv1.5 is considered to be a potential molecular target for treatment of atrial fibrillation or flutter. Disopyramide is widely used in the treatment of atrial flutter and/or atrial fibrillation. The present study was undertaken to characterize the effects of disopyramide on currents mediated by Kv1.5 channels and to determine the putative binding site involved in the inhibitory effects of disopyramide. Experiments were carried out on wild-type and site directed mutated hKv1.5 channels expressed on HEK 293 cells using the patch-clamp technique. Disopyramide acting from the cytoplasmic side of the membrane produced blocking effects on Kv1.5 that exhibited several features typical of an open channel blocker. Ala-scanning mutagenesis of the Kv1.5 pore domain combined with macroscopic current analysis suggested that disopyramide interacted only with the Val512 residue that faces to the central cavity of the channel. Mutation of this key residue to Ala caused marked change in the IC50 of disopyramide (22-fold). The single interaction between disopyramide and Val512 in the PVP region is able to change the mechanism of channel closure, reproducing the "foot-in-the-door" phenomenon. Keywords:: potassium channel, ultra rapid delayed rectifier, Kv1.5, antiarrhythmic, disopyramide